The mouse alpha-globin locus regulatory element. - Gourdon, G; Sharpe, J; Higgs, D; Wood, W (1995)
We have identified and cloned the major alpha globin locus regulatory element in the mouse (m alpha RE). This element shows a high level of sequence homology to its human counterpart (HS -40) and lies between the same two exons of an upstream, widely expressed gene in both species. Footprinting and band shift studies of the core element show conservation of many (but not all) of the protein binding sites identified as functionally important in HS -40. The functional equivalence of the mouse element was shown by attaching it to a human alpha globin gene and examining expression in transgenic mice. Readily detectable levels of human alpha mRNA were produced in these mice but they were lower than the endogenous gene expression and did not show copy number dependence. These results suggest that sequences additional to this major regulatory element may be necessary to obtain complete regulation of the alpha globin genes in both species.